Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Advances in Materials Science and Engineering, 2017)

Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices. - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
In this work, polycaprolactone (PCL) was used as a basic polymer for electrospinning of random and aligned nanofiber matrices. Our aim was to develop a biocompatible substrate for ophthalmological application to improve wound closure in defects of the cornea as replacement for human amniotic membrane. We investigated whether blending the hydrophobic PCL with poly (glycerol sebacate) (PGS) or chitosan (CHI) improves the biocompatibility of the matrices for cell expansion. Human corneal epithelial cells (HCEp) and human corneal keratocytes (HCK) were used for in vitro biocompatibility studies. After optimization of the electrospinning parameters for all blends, scanning electron microscopy (SEM), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), and water contact angle were used to characterize the different matrices. Fluorescence staining of the F-actin cytoskeleton of the cells was performed to analyze the adherence of the cells to the different matrices. Metabolic activity of the cells was measured by cell counting kit-8 (CCK-8) for 20days to compare the biocompatibility of the materials. Our results show the feasibility of producing uniform nanofiber matrices with and without orientation for the used blends. All materials support adherence and proliferation of human corneal cell lines with oriented growth on aligned matrices. Although hydrophobicity of the materials was lowered by blending PCL, no increase in biocompatibility or proliferation, as was expected, could be measured. All tested matrices supported the expansion of human corneal cells, confirming their potential as substrates for biomedical applications.

Analyzing the transmission of visible light through electrospun nanofibrous PCL scaffolds - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Helsinki (Finland), 2021, 2021)

A novel suture retention test for scaffold strength characterization in ophthalmology. - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2016)
Sutures are a common way to attach scaffolds in patients. For tubular cardiac scaffolds, the 'suture retention strength' is commonly used to evaluate the resistance of a scaffold against the pull-out of a suture. In order to make this quantity accessible for ophthalmological scaffolds the test procedure has been modified in a novel way. Polycaprolactone (PCL) films of different thicknesses and an amniotic membrane (AM) were used for the experiments. Circular samples with a radius of 7mm were taken and a suture was passed through each sample and tied to a loop. The sample was clamped in a tensile tester and a bolt was passed through the loop. The suture was then pulled with a constant deformation rate until pull-out occurred. The suture retention strength, the deformation at the suture retention strength, and the deformation at rupture were determined for each sample. The presented modified suture retention test allows to measure the relevant parameters of samples on the scale of ophthalmological scaffolds in a reproducible way. A comparison between the first data on PCL and AM has been made.

Argon Cold Plasma–A Novel Tool to Treat Therapy-resistant Corneal Infections - Reitberger, Helena; Czugala, Marta; Chow, Catherine; Mohr, Andreas; Burkovski, Andreas; Gruenert, Anja K.; Schoenebeck, Renate; Fuchsluger, Thomas (American Journal of Ophthalmology, 2018)

Biomaterialien als DMEK-& Amnionmembranersatz - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (2. Baltic Sea Eye Conference, Rostock (Deutschland), 2020, 2020)

Biomechanical assessment of healthy and keratoconic corneas (with/without crosslinking) using dynamic ultrahigh-speed Scheimpflug technology and the relevance of the parameter (A1L-A2L) - Fuchsluger, Thomas; Brettl, Susanne; Geerling, Gerd; Kaisers, Wolfgang; Zeitz, Philipp Franko (British Journal of Ophthalmology, 2019)
Aims To examine corneal biomechanics in healthy and keratoconic eyes, with or without crosslinking obtained by ultrahigh-speed Scheimpflug measurements (Corvis ST).
CRIS-Team WoS Importer:2019-07-02

Cornea: endothelial dystrophies and degenerations - Fuchsluger, Thomas; Lisch, W; Geerling, G; Seitz, B (Klinische Monatsblätter für Augenheilkunde, 2015)
EVALuna2:21220

Corneal endothelium can be protected against cell by anti-Bax siRNA - Fuchsluger, Thomas; Thieme, Daniel; Kruse, Friedrich; Mahajan, Siddharth; Schubert, Dirk W. (The Association for Research in Vision and Ophthalmology (ARVO), 2018)
Keywords: corneal; ani-Bak

Corneal endothelium can be protected against cell death by anti-Bax and anti-Bak siRNA - Fuchsluger, Thomas; Thieme, Daniel; Kruse, Friedrich; Mahajan, Siddharth (2018)
EVALuna2:34735

Critical endothelial procedures during posterior lamellar graft preparation and transplantation - Fuchsluger, Thomas; Kruse, Friedrich Eduard; Geerling, G. (Ophthalmologe, 2017)
In view of the very low proliferation rate and functional importance of the corneal endothelium in maintaining corneal transparency, safeguarding the integrity of this monolayer plays a central role in posterior lamellar corneal transplantation. Several critical endothelial procedural stages are necessary to carry out such a transplantation.This article presents various preparatory and operative approaches for carrying out the necessary and critical stages within the framework of posterior lamellar corneal transplantation and concentrates on the question of optimization.A review of our own studies and studies of other groups is presented.For the performance of critical endothelial procedural steps, a variety of approaches are available. These range from preparation and insertion of the transplant, through the manipulation during centralization up to the effects of postoperative air or gas bubble tamponade.Because endothelial damage can permanently impair the integrity of lamellar transplants, a minimal handling and no touch policy should be strived for in all critical procedures. Long-term data on the follow-up course will show which of the procedures favored by various authors lead to the best postoperative results.
EVALuna2:21276

Descemet membrane endothelial keratoplasty as treatment for graft failure after descemet stripping automated endothelial keratoplasty - Weller, Julia M.; Tourtas, Theofilos; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula; Fuchsluger, Thomas; Bachmann, Bjoern O. (American Journal of Ophthalmology, 2015)
To investigate the outcome of Descemet membrane endothelial keratoplasty (DMEK) in patients with graft failure after Descemet stripping automated endothelial keratoplasty (DSAEK).Retrospective cohort study.setting: Institutional.Fifteen eyes of 15 patients that underwent DMEK for graft failure with corneal decompensation following DSAEK were analyzed; 15 eyes with primary DMEK for Fuchs corneal dystrophy were included as control group.Best-corrected visual acuity (BCVA), endothelial cell density (ECD), central corneal thickness (CCT), and rebubbling rate.DMEK surgery was successful in all cases of both groups. Mean BCVA (logMAR) before DMEK was 1.27 ± 0.34 in the DMEK after DSAEK group and 1.0 ± 0.40 in the Primary DMEK group. After DMEK, mean BCVA increased significantly to 0.23 ± 0.21 (P = .012, DMEK after DSAEK group) and 0.29 ± 0.23 (P = .042, Primary DMEK group) after 3 months. There were no significant differences in mean BCVA between both groups at each visit. The rebubbling rate was 13% in the DMEK after DSAEK group and 40% in the Primary DMEK group (P = .1). Mean CCT decreased significantly in both groups 1 month after DMEK (P < .05). Mean ECD and change of ECD did not differ significantly between both groups at each visit (P > .05).The results after DMEK as a procedure to treat graft failure after DSAEK were as good as in patients that underwent DMEK as primary intervention to treat advanced Fuchs dystrophy. This indicates that the optical quality can be reestablished by DMEK in patients with failed DSAEK.
EVALuna2:21229

Designing novel scaffolds for ocular surface reconstruction based on aligned nanofibers - Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Polychar, 2017)

Efficient and safe gene delivery to human corneal endothelium using magnetic nanoparticles - Czugala, Marta; Mykhaylyk, Olga; Boehler, Philip; Onderka, Jasmine; Stork, Boejrn; Wesselborg, Sebastian; Kruse, Friedrich; Plank, Christian; Singer, Bernhard B.; Fuchsluger, Thomas (Nanomedicine, 2016)
To develop a safe and efficient method for targeted, anti-apoptotic gene therapy of corneal endothelial cells (CECs).Magnetofection (MF), a combination of lipofection with magnetic nanoparticles (MNPs; PEI-Mag2, SO-Mag5, PalD1-Mag1), was tested in human CECs and in explanted human corneas. Effects on cell viability and function were investigated. Immunocompatibility was assessed in human peripheral blood mononuclear cells.Silica iron-oxide MNPs (SO-Mag5) combined with X-tremeGENE-HP achieved high transfection efficiency in human CECs and explanted human corneas, without altering cell viability or function. Magnetofection caused no immunomodulatory effects in human peripheral blood mononuclear cells. Magnetofection with anti-apoptotic P35 gene effectively blocked apoptosis in CECs.Magnetofection is a promising tool for gene therapy of corneal endothelial cells with potential for targeted on-site delivery.
EVALuna2:21292

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (30th Annual Conference of the European Society for Biomaterials, Dresden (Deutschland), 2019, 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (16th Bayreuther Polymer Symposium, Bayreuth (Deutschland), 2019., 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Trondheim (Norwegen), 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (The Association for Research in Vision and Ophthalmology (ARVO), 2019)

Gene Therapy for Modulation of T Cell Mediated Immune Response Provoked by Corneal Transplantation - Pastak, Marko; Kleff, Veronika; Saban, Daniel R.; Czugala, Marta; Steuhl, Klaus-Peter; Erguen, Sueleyman; Singer, Bernhard B.; Fuchsluger, Thomas (Human Gene Therapy, 2017)
Corneal transplantation (=keratoplasty) is the most common type of tissue replacement in the world. The increased rate of graft rejection after keratoplasty is a central problem for repeated transplantations and in inflamed host corneas. It has been shown that apoptosis of grafted epithelium has a role in corneal allograft rejection. Our study focused on the T cell response triggered in BALB/c mice after allogeneic corneal transplantation with and without anti-apoptotic p35-transduced epithelium. To restrict p35 expression to the epithelial cells we created modified allogeneic composite grafts. As a result we found that the proportion of alloreactive CD4+ T cells in postoperatively removed cervical lymph nodes was reduced in the p35-transduced group compared to the allogeneic control group. Diminished priming of the CD4+ T cells was supported by significantly decreased proliferation and lower interferon gamma secretion when compared to allogeneic engraftments. The reduced priming of CD4+ lymphocytes is the first confirmation of the functionality of p35 in the epithelium of corneal grafts to alter the development of the recipient's immune response. Thus, modification of allosensibilization seems to be a promising tool for reducing graft-mediated immune response following corneal transplantation.
EVALuna2:21342

Identification of Process Limits for Electro-Spinning of aligned – Nano Fibres of the CPL/PGS 1: 1 blend - Bischoff, S.; Küng, Florian; Stafiej, Piotr; Fuchsluger, Thomas; Boccaccini, Aldo R.; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Identifying Design Principles for the Transmission of Visible Light through Electrospun Nanofibrous PCL Scaffolds for Corneal Tissue Engineering - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (4. Baltic Sea Eye Conference, Rostock (Deutschland), 2022, 2022)

Identifying key parameters for the transmission of visible light through electrospun nanofibrous PCL scaffolds for ophthalmic applications - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (31th Annual Conference of the European Society for Biomaterials, Porto (Portugal), 2021, 2021)

Influence of operating parameters on the suture retention test for scaffolds in ophthalmology - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
The strength of a suture used to attach a graft to a patient can be quantified using the suture retention test. In order to gain deeper insight on the influence of testing and application conditions testing parameters were varied. Different pull rates, suture and jaw positions, and suture materials were tested to show their influence on the result of the test. The results of the different states were analyzed using statistical tests. Based on the statistic analysis conditions for testing with a maximum of accuracy and as close as possible to in vivo conditions have been revealed.
EVALuna2:21344

Influence of the molar mass distribution on the suture-ability of nanofiber meshes for tissue engineering - Hehn, Markus; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

Influence of the molecular weight on the suture retention properties of polycaprolactone - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Instrument to Enhance Visualization of Descemet Membrane During Graft Preparation for DMEK Surgery - Menzel-Severing, Johannes; Salla, Sabine; Plum, Wolfgang Joachim; Tourtas, Theofilos; Fuchsluger, Thomas; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich Eduard (Cornea, 2016)
Descemet membrane (DM) endothelial keratoplasty has improved outcomes of corneal transplantation in patients with corneal endothelial disease. However, the procedure has been criticized for jeopardizing donor tissue during graft preparation. Standardization of this procedure may provide a way toward minimizing tissue loss. For this purpose, we propose the use of a novel tool.Computerized numerical control milling was used to create a blunt instrument, which was used to remove endothelial cells within a defined area in the periphery of donor corneas. Trypan blue was used to stain denuded DM. Graft preparation was continued as per our standard protocol. Transmission electron microscopy was performed on the treated area, and endothelial cell counts were obtained.Use of the modified procedure resulted in delineation of a peripheral band of denuded DM, which readily stained with trypan blue. This provided increased visibility of DM during subsequent steps. Transmission electron microscopy confirmed that no structural deficits of DM were induced. Mean endothelial cell loss (±SD) at 24 hours after preparation was 63 (±130) cells per square millimeter in the group prepared with the use of the new instrument (n = 7), versus 116 (±107) cells per square millimeter in the group prepared without the new instrument (n = 7; P = 0.45).The device presented here enhances visualization of DM during creation of the peripheral margin for subsequent lifting of the margin and stripping of the graft. This may increase success rates and shorten preparation times and learning periods for DM preparation. DM ultrastructure and endothelial cells were not negatively affected.
EVALuna2:21287

Mapping of the electrospinning parameters for PLGA-Nanofibers - Regelmann, Christian; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

Nanofaserscaffolds als DMEK-& Amnionmembranersatz – Anforderungen und Eigenschaften - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (iSearch 2021, Münster (Deutschland), 2021, 2021)

New possibilities for ocular surface reconstruction : Collagen membranes and biocompatible elastomer nanofibers - Fuchsluger, Thomas; Salehi, S.; Petsch, Christina; Bachmann, B. (Ophthalmologe, 2014)
Amniotic membranes have been used for many years for reconstruction of the ocular surface. Despite having anti-inflammatory and antiangiogenic properties as well as being suitable as a carrier for corneal epithelial cells, amniotic membranes also have some limitations for use at the human cornea: availability is limited, there are major interindividual variations in structure and growth factor content and are not free from the risk of disease transmission. Progress in tissue engineering has been made aiming at the development and improvement of alternative biomaterials.This article presents new approaches for reconstruction of the corneal surface with collagen-based biomaterials and polymers.Electronic databases were searched for articles which evaluated collagenous biomaterials for use at the corneal surface. In addition the authors' own experiences with novel biomaterials are described.In vitro evaluation of the described biomaterials suggested a high biocompatibility with corneal epithelial cells in cell cultures. In vivo experiments with these materials in animal corneas demonstrated a certain variability in degradation and remodeling. Although some materials showed promising experimental results none of these are established in the clinical routine and only few clinical studies have so far been conducted with collagen-based biomaterials.Although the majority of the described biomaterials are currently still in the experimental stage, a transfer into the clinical routine is conceivable and of great therapeutic interest.
EVALuna2:21193

Non-linear imaging as tool in biomaterials research - Thieme, Daniel; Fuchsluger, Thomas; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien - Annual Meeting, 2018)
Keywords: biomaterial; bioprinting

Novel biomaterials for ocular surface surgery - Thieme, Daniel; Fuchsluger, Thomas; Schubert, Dirk W. (Acta Ophthalmologica, 2018)

Novel concepts for treatment of the corneal endothelium with nanoparticles - Fuchsluger, Thomas (Ophthalmologe, 2018)
The number of corneal transplantations has increased in Germany in recent years. One reason is an earlier time point of surgery due to less invasive posterior lamellar grafting techniques. To date, penetrating and lamellar corneal transplantations are the only established therapeutic options to treat corneal diseases resulting from endothelial cell pathologies.This review article provides an insight into nanoparticle-related translational strategies to improve or to avoid corneal transplantation.Nanoparticle-based strategies for optimization of the corneal endothelium have different fields of application: 1. during donor cornea cultivation in culture medium, 2. for single cell injection therapies and 3. to treat the patients' own endothelium in an effort to avoid transplantation.Several translational concepts exist to improve or to avoid grafting of a donor cornea. The coming decade will provide established alternatives to conventional corneal transplantation.
EVALuna2:21361

Optimized human platelet lysate as novel basis for a serum-, xeno- and additive-free corneal endothelial cell and tissue culture - Thieme, Daniel; Reuland, Lynn; Lindl, Toni; Kruse, Friedrich; Fuchsluger, Thomas (Journal of Tissue Engineering and Regenerative Medicine, 2017)
The expansion of donor derived corneal endothelial cells is a promising approach for regenerative therapies in corneal diseases. To achieve the best GMP standard the entire cultivation process should be devoid of non-human components. However, so far there is no suitable xeno-free protocol for clinical applications.We therefore introduce a processed variant of a platelet lysate for the use in corneal cell and tissue culture based on a GMP-grade thrombocyte concentrate. This processed human platelet lysate (phPL), free of any animal components and of anti-coagulants like heparin with a physiological ionic composition, was used to cultivate corneal endothelial cells (EC) in vitro and ex vivo in comparison to standard cultivation with FCS. Human donor corneas were cut in quarters while two quarters of each cornea were incubated with the respective medium supplement. Three fields of view per quarter were taken into account for the analysis.Evaluation of phPL as a medium supplement in cell culture of immortalized EC showed a superior viability compared to fetal calf serum (FCS) control with reduced cell proliferation. Furthermore, the viability during the expansion of primary cells is significantly (3fold+-0.5) increased with phPL compared to FCS standard medium. Quartering donor corneas was traumatic for the endothelium and therefore resulted in increased EC loss. Interestingly, however, cultivation of the quartered pieces for two weeks in 0.1mg/mL pHPL in Biochrome I showed a 21 (+-10) % EC loss compared to 67 (+-12) % EC loss when cultivated in 2% FCS in Biochrome I.The cell culture protocol with pHPL as FCS replacement seems to be superior to the standard FCS protocols with respect to EC survival. It offers a xeno-free and physiological environment for corneal endothelial cells. This alternative cultivation protocol could facilitate the use of EC for human corneal cell therapy.
EVALuna2:21343

Poly (glycerol sebacate)-poly (?-caprolactone) blend nanofibrous scaffold as intrinsic bio- and immunocompatible system for corneal repair - Salehi, Sahar; Czugala, Marta; Stafiej, Piotr; Fathi, Mohammadhossein; Bahners, Thomas; Gutmann, Jochen S.; Singer, Bernhard B.; Fuchsluger, Thomas (Acta Biomaterialia, 2017)
A major challenge in corneal tissue engineering and lamellar corneal transplantation is to develop synthetic scaffolds able to simulate the optical and mechanical properties of the native cornea. As a carrier, the graft scaffolds should provide the basis for anchorage, repair and regeneration. Although quite a number of scaffolds have been engineered to date, they have not been able to simultaneously recapitulate chemical, mechanical, and structural properties of the corneal extracellular matrix (ECM). Here, we examined different compositions of elastomeric biodegradable poly (glycerol sebacate) (PGS)-poly (?-caprolactone) (PCL) nanofibrous scaffolds with respect to their cyto- and immunocompatibility. These scaffolds were semi-transparent with well-defined mechanical properties and direct positive effects on viability of human corneal endothelial cells (HCEC) and human conjunctival epithelial cells (HCjEC). Moreover, within 3days HCEC established monolayers with the hexagonal morphology typical for this cell type. All PGS-PCL mixtures analyzed did not trigger effects in granulocytes, naïve and activated peripheral blood mononuclear cells (PBMCs). However, scaffolds with a higher content of PGS-PCL ratio showed the best cell organization, cyto- and immunocompatibility. Subsequently, this PGS-PCL composition could be used for further development of clinical constructs to support corneal tissue repair.In corneal tissue engineering a major challenge is the development of synthetic scaffolds with similar properties to native cornea. In our recent works, we introduced the biodegradable, polymeric nanofibrous scaffolds with similar optical and mechanical properties for corneal regeneration and here we examined the cyto- and immunocompatibility of biodegradable nanofibrous scaffolds in contact to white blood cells. Directing the alignment of human corneal cells by nanofibrous scaffolds and high viability of cells was detected by forming of endothelium monolayer with hexagonal morphology on the nanofibrous scaffold. In addition, our results for the first time show that these nanofibrous scaffolds did not trigger effects in white blood cells. These results highlight the considerable translational potential of the nanofibrous scaffolds to clinical applications.
EVALuna2:21330

Protection of corneal endothelium from apoptosis by gene and cell therapy - Fuchsluger, Thomas (Ophthalmologe, 2016)
Protection of corneal endothelium from apoptosis using gene and cell therapy is in a translational phase. This approach offers advantages for eye banking and after transplantation. Safe vehicles for gene or cell therapeutic transduction of corneal endothelium with nucleic acids are available. This strategy will be further developed in consultation with the Paul Ehrlich Institute and European regulatory authorities.
EVALuna2:21284

Self-Complementary Adeno-Associated Virus Vectors Improve Transduction Efficiency of Corneal Endothelial Cells - Gruenert, Anja K.; Czugala, Marta; Mueller, Chris; Schmeer, Marco; Schleef, Martin; Kruse, Friedrich; Fuchsluger, Thomas (PLoS ONE, 2016)
Transplantation of a donor cornea to restore vision is the most frequently performed transplantation in the world. Corneal endothelial cells (CEC) are crucial for the outcome of a graft as they maintain corneal transparency and avoid graft failure due to corneal opaqueness. Given the characteristic of being a monolayer and in direct contact with culture medium during cultivation in eye banks, CEC are specifically suitable for gene therapeutic approaches prior to transplantation. Recombinant adeno-associated virus 2 (rAAV2) vectors represent a promising tool for gene therapy of CEC. However, high vector titers are needed to achieve sufficient gene expression. One of the rate-limiting steps for transgene expression is the conversion of single-stranded (ss-) DNA vector genome into double-stranded (ds-) DNA. This step can be bypassed by using self-complementary (sc-) AAV2 vectors. Aim of this study was to compare for the first time transduction efficiencies of ss- and scAAV2 vectors in CEC. For this purpose AAV2 vectors containing enhanced green fluorescent protein (GFP) as transgene were used. Both in CEC and in donor corneas, transduction with scAAV2 resulted in significantly higher transgene expression compared to ssAAV2. The difference in transduction efficiency decreased with increasing vector titer. In most cases, only half the vector titer of scAAV2 was required for equal or higher gene expression rates than those of ssAAV2. In human donor corneas, GFP expression was 64.7±11.3% (scAAV) and 38.0±8.6% (ssAAV) (p<0.001), respectively. Furthermore, transduced cells maintained their viability and showed regular morphology. Working together with regulatory authorities, a translation of AAV2 vector-mediated gene therapy to achieve a temporary protection of corneal allografts during cultivation and transplantation could therefore become more realistic.
EVALuna2:21299

Suture-ability of patch grafts for ocular surface reconstruction - Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Polychar, 2017)

Suture retension test method for opthalmological materials - Voigt, Monika; Thieme, Daniel; Küng, Florian; Schubert, Dirk W.; Kruse, Friedrich; Fuchsluger, Thomas (Deutsche Gesellschaft für Biomaterialien, 2018)
Keywords: biomaterialien; espinning suture retension

The influence of donor factors on corneal organ culture contamination - Gruenert, Anja K.; Rosenbaum, Katja; Geerling, Gerd; Fuchsluger, Thomas (Acta Ophthalmologica, 2017)
To evaluate the contamination rate and the corresponding spectrum of microbes and to identify donor risk factors for corneal organ culture contaminations.A total of 3306 organ-cultured donor corneas were included in the study. We performed a retrospective database analysis to evaluate donor factors such as gender, age, death-to-explantation interval (DEI), procurement site and cause of death and to determine their influence on donor cornea contaminations. Odds ratios (ORs) were calculated for each factor.The overall contamination rate was 7.8% (n = 259). Younger donor age (OR: 2.2, p = 0.003, chi-squared test), a DEI of more than 24 hr (OR: 1.6, p < 0.001), hospitalization prior to death (OR: 2.2, p < 0.001) and death caused by sepsis (OR: 2.7, p < 0.001) were associated with an increased risk of contamination, whereas donor gender did not have an effect on donor cornea contaminations. The most frequently isolated microbes were Enterococci (19%), Staphylococci (10.8%) and Candida (37.4%).This study helps to estimate the contamination risk of a cultured cornea based on specific donor factors. However, donors with risk factors should not be generally excluded from cornea donation. Further studies including antibiograms might clarify whether a change in the antibiotic composition of the culture medium would be useful to deal with the increasing number of multi-resistant microbes.
EVALuna2:21327

Therapy-associated corneal pathologies - Fuchsluger, Thomas; Geerling, G. (Ophthalmologe, 2017)
EVALuna2:21345

Transparency of nanofiber reinforced alginate hydrogels for corneal wound healing - Stafiej, Piotr; Küng, Florian; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Transparency of suture able polycaprolactone nanofiber hydrogel compounds for medical application in the eye - Stafiej, Piotr; Fuchsluger, Thomas; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

Transparency of suture able polycaprolactone nanofiber hydrogel compounds (NFHC) for medical application in ophthalmology - Stafiej, Piotr; Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien 2017, 2017)